2013
DOI: 10.4103/0019-5413.108917
|View full text |Cite
|
Sign up to set email alerts
|

Tru-cut biopsy as the initial method of tissue diagnosis in bone tumors with soft tissue extension

Abstract: Background:Tru-cut biopsy in suspected bone tumors can be performed even in less specialized centers. Tru-cut biopsy has been proved as safe with more than 90% accuracy. However, its usefulness was not widely studied in general hospitals where Tru-cut biopsy is performed by orthopedic surgeons. This study was conducted to find out the accuracy and adequacy of Tru-cut biopsy performed by an orthopedic surgeon not trained in musculoskeletal oncology, in a general hospital.Materials and Methods:A study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
2
12
0
2
Order By: Relevance
“…Palpe edilen yumuşak doku komponenti olan lezyonlarda yardımcı görüntüleme yöntemleri kullanılmadan başarılı bir şekilde yapılabilir. [2] Ulaşılması zor olan bölgelere (pelvis, vertebra) BT, MR ve US eşliğinde ulaşma olanağı sağlar (Şekil 4). [10][11][12] Metastatik lezyon, enfeksiyon ve lokal nüks olan tümörlerde doğruluğu en yüksek iken, deneyimsiz bir cerrah tarafından yapılması teknik olarak zordur ve tümör hücrelerinin sağlıklı dokulara bulaşmasına neden olabilir.…”
Section: Kapalı Biyopsiunclassified
See 1 more Smart Citation
“…Palpe edilen yumuşak doku komponenti olan lezyonlarda yardımcı görüntüleme yöntemleri kullanılmadan başarılı bir şekilde yapılabilir. [2] Ulaşılması zor olan bölgelere (pelvis, vertebra) BT, MR ve US eşliğinde ulaşma olanağı sağlar (Şekil 4). [10][11][12] Metastatik lezyon, enfeksiyon ve lokal nüks olan tümörlerde doğruluğu en yüksek iken, deneyimsiz bir cerrah tarafından yapılması teknik olarak zordur ve tümör hücrelerinin sağlıklı dokulara bulaşmasına neden olabilir.…”
Section: Kapalı Biyopsiunclassified
“…Uygun olmayan biyopsi tedaviye yarardan daha çok zarar vereceğinden temel eğitimin alınmış olması veya asıl tedaviyi üstlenecek merkezlerde yapılması şarttır. [1,2] Multidisipliner yaklaşım olmadan verilmiş biyopsi kararı bazen gereksiz yere bazen de yanlış yerden örnek alınmasına neden olabilir. Asıl tedavide kullanılacak insizyonun dışında bir insizyon kullanılması ya da alınmış örneği değerlendiren patoloji uzmanına doğru klinik bilgi verilmemesi, dönüşü olmayan hatalara yol açabilir.…”
unclassified
“…Joshi A et al found the sensitivity and specificity of Tru-cut biopsy of palpable bone lesions with soft tissue extension in their series was 92.85% and 100%, respectively, with positive predictive value of 100% and negative predictive value of 57.14%. 1 However guided biopsies are becoming popular as they can hit the lesion more accurately in many cases. Ultrasound guided tru-cut biopsies were done by Saifiddin et al in lesions with relatively large extraosseous component.…”
Section: Discussionmentioning
confidence: 99%
“…It is very important to differentiate between benign and malignant conditions before treating it. Diagnosis and treatment involves team of specialists involving pathologists, radiologists, surgeons in managing the bone tumours [1][2][3][4] . Preoperative histopathological diagnosis is corner stone, which are most definitive methods of preoperative diagnosis [4][5][6].…”
Section: Introductionmentioning
confidence: 99%